Analisis Pengaruh Penerapan Prinsip Good corporate governance Terhadap Pengelolaan Dana Desa oleh Pemerintah Desa (Studi Kasus di Desa Sampangagung Kecamatan Kutorejo Kabupaten Mojokerto) - Linda Erika; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2023)
This research was conducted with the aim of analyzing the effect of applying the principles of good corporate governance on the management of village funds. The type of research used in this research is qualitative research with a descriptive approach. Sources of data used are secondary data and primary data. Collecting data by means of interviews and documentation. This research was conducted in Sampangagung Village, Kutorejo District, Mojokerto Regency. In the application of the principles of Good corporate governance, it has been going quite well because its implementation is in accordance with the applicable laws, but there are still many deficiencies that must be corrected by the village government. The principles that have now been implemented are the principle of accountability, the principle of responsibility, the principle of fairness and what has not been fully implemented is the principle of transparency because village financial reports and information about Sampangagaung Village can only be obtained if we go to the Sampangagung Village office because there are no websites and social media that can be used to access information about Sampangagung Village.Keywords: good corporate governance., accountability, management of village funds